Refocusing the EU Budget - An Institutional View - Charles B. Blankart; Gerrit B. Koester (Center for Research in Economics, Management and the Arts (CREMA), 2009)
There is little disagreement that the EU budget should be refocused. Redistributive agricultural and structural spending should be reduced in favour of more public good spending as the Boege and Sapir reports demand. But a public choice analysis can show that the current deadlock makes a refocusing of the budget unlikely. Starting with the Treaty of Rome we demonstrate how Member States became net payers and receivers and why the underlying coalitions were fairly stable and will remain so after Lisbon. We propose an additional public good budget within an improved process of enhanced cooperation to overcome the deadlock.
Keywords: H31; D78; H87; 330